Genome editing of the eukaryotic translation initiation factors (eIF) in maize - CGIAR Research Program on Maize (2021)
Obtained mutant gene in each of the four targeted eIF members by editing directly in CML536, an MLN susceptible line from eastern Africa. Identified two eIF that confer MLN resistance when knocked out. The line ready to test in the field.